A rat model of pre-puberty (Juvenile) stress-induced predisposition to stress-related disorders: Sex similarities and sex differences in effects and symptoms. (January 2014) - Horovitz, O.; Tsoory, M.M.; Yovell, Y.; Richter-Levin, G.
Abstract Objectives. This study assessed the interactive effect of two risk factors: "Juvenile stress" and sex in the long-term consequences of "Juvenile stress" in male and female rats. Methods. Rats were exposed to "Juvenile stress" and to additional stress in adulthood. Measurements of anxiety and depressive-like behaviours were assessed in relation to each stress exposure and "Sex-specific" sets of criteria in order to characterize individual profiles of altered behaviours. Results. While both male and female rats were affected by exposure to "Juvenile stress", sex difference were evident in saccharine preference, coping with the stressful challenge of the two-way shuttle avoidance task, and on "Adult stress" induced changes in saccharine preference. "Profiling" altered behaviours revealed sex differences also in the prevalence of rats exhibiting different categories of "Affected" behaviours, indicating that female rats are more susceptible to the long-term effects of "Juvenile stress" and to the immediate effects of "Adulthood stress". Additionally, the prevalence of "Affected" animals among "Juvenile+ Adulthood stress" was similar, yet the profile of altered behaviours was significantly different. Conclusions. The "Behavioural Profiling" approach presented here is of importance to understanding gender differences in the aetiology of predisposition to stress-related disorders, and of gender symptomatology differences in stress-related disorders.